Canadian churches and the First World War - Heath, Gordon L. (The Lutterworth Press, 2014)
Most accounts of Canada and the First World War either ignore or merely mention in passing the churches' experience. Canadian Churches and the First World War addresses this surprising neglect, exploring the marked relationship between Canada's 'Great War' and Canadian churches in intricate detail.The authors of this volume provide a detailed summary of various Christian traditions and the war, both synthesising and furthering previous research. In addition to examining the experience of Roman Catholics (English and French speaking), Anglicans, Presbyterians, Methodists, Baptists, Lutherans, M.